2013
DOI: 10.18561/2179-5746/biotaamazonia.v3n3p193-197
|View full text |Cite
|
Sign up to set email alerts
|

Length–Length and Length–Weight Relationships for Fish Fauna from Headwaters of Onça Puma Mountain Ridge, Amazonian Region, Brazil

Abstract: Length-length (LLR) and length-weight (LWR) relationships are presented for 19 fish species collected between 2009 and 2011 in small tributaries and headwaters areas of the Tocantins-Araguaia basin, Itacaiúnas drainage, Southwestern Pará, Amazonian, Brazil. This study describes the first reference of LLR for 13 species and LWR for 16 fish species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
4
3
Order By: Relevance
“…Compared with published data, O. niger and A. robertsi had maximum length values higher than those observed in the Xingu River (Giarrizzo et al., ). The same occurred for G. neambi in relation to headwater stream specimens sampled in the Amazon Basin (Oliveira, Andrade, Piteira, & Giarrizzo, ). For all species in the present study, the maximum lengths were greater than the values reported in Fishbase, which highlights the importance of constantly updating data.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Compared with published data, O. niger and A. robertsi had maximum length values higher than those observed in the Xingu River (Giarrizzo et al., ). The same occurred for G. neambi in relation to headwater stream specimens sampled in the Amazon Basin (Oliveira, Andrade, Piteira, & Giarrizzo, ). For all species in the present study, the maximum lengths were greater than the values reported in Fishbase, which highlights the importance of constantly updating data.…”
Section: Discussionsupporting
confidence: 63%
“…The maximum length difference in O. niger could be explained by the larger number of analyzed specimens herein (34) compared to the Xingu River (12) (Giarrizzo et al., ). For G. neambi , the largest size recorded here might be related to the sampling sites, as we took samples in the main channel rather than in small tributaries (Oliveira et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to smaller samples sizes (< 20 individuals) LWR's should be treated with caution for Triportheus albus and Pimelodus blochii. Growth type did not differ significantly between juvenile and adult individuals for those 6 species in the present study, but the allometry results for six species showed distinct growth type found in previous research (FROESE;PAULY, 2014;GIARRIZZO et al, 2011GIARRIZZO et al, , 2015OLIVEIRA et al, 2013) based on LWR done with TL. We assume that the use of standard length for LWR regressions, which revealed lower data variation and thus greater statistical robustness than TL for our fish samples, is a possible explanation for such differences.…”
Section: Discussioncontrasting
confidence: 63%
“…Ruffino, Issac (1995) estimated a slope value of 3.18 in Brazil, compared to 2.85 estimated for the Ecuadorian population. However, elsewhere in Brazil (e.g., Araguaia River, Tocantins basin), the slope value was only 2.45 for black prochilodus (Sena- Oliveira et al, 2013). Estimates of the LW relationship in eight floodplain lakes along the middle and lower Solimões River in Brazil ranged from 2.26-2.45 for this same species (Tribuzy-Neto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%